CARBON ACCOUNTING AS A FORM OF ENVIRONMENTAL ACCOUNTABILITY: A PHENOMENOLOGICAL STUDY ON THE RENEWABLE ENERGY COMPANY - Candra Pramula Pinandita; Dwi Indriani Fidiastutik Wijaya; Eti Putranti (Worksheet : Jurnal Akuntansi, 2026)
This research aims to analyze the practices and meanings of carbon accounting as a form of environmental accountability in renewable energy companies, with a phenomenological study on PT Pertamina Geothermal Energy Tbk (PGEO). The background of the research is based on the increasing demand for transparency and environmental accountability amid the energy transition and national carbon emission reduction commitments. This research uses a qualitative approach with a phenomenological method within an interpretive paradigm. Research data were obtained thru the analysis of organizational documents such as sustainability reports, annual reports, and carbon emission management policies. The data analysis technique was conducted using Interpretative Phenomenological Analysis (IPA) with a focus on the dimensions of noema, noesis, and intentionality. The research results show that carbon accounting at PGEO is realized thru the systematic disclosure of Scope 1, Scope 2, and Scope 3 emissions that align with international reporting standards. Structural analysis reveals that carbon reporting practices are interpreted as a strategic instrument in maintaining the legitimacy and credibility of the company amidst ESG and capital market pressures. Meanwhile, the analysis of intentionality shows that carbon accounting is not merely understood as an administrative formality, but as a substantial and data-driven form of environmental accountability. This study concludes that carbon accounting plays a crucial role in ensuring consistency between sustainability claims and the operational realities of renewable energy companies. These findings are expected to enrich the study of environmental accounting and encourage more transparent and responsible carbon reporting practices in the renewable energy sector.